Effectiveness of mental empowerment training program on increasing teachers’ psychological capital and job-related affective well-being - Mona Valeh; Omid Shokri; Hasan Asadzadeh (مجله علوم روانشناختی, 2021)
Background: Recent studies allude to an increasing trend in teachers to retire early from their profession and pay less attention to maintaining a health-oriented, occupational lifestyle. This highlights the need to develop psycho-educational interventions aimed at strengthening psychological capital in teachers. Aims: This study was aimed to investigate the effectiveness of empowerment training program to increase psychological capital and emotional well-being related to the job of a group of female teachers. Method: The present research was quasi-experimental with pretest, posttest, control group design and two-month follow-up period. The statistical population of the study included all female teachers of the first and second course of secondary school in the 4th educational region of Tehran in the first semester of the 99-98 academic year. Among them, 60 female teachers in experimental (n=30) and control (n=30) groups who were selected by convenience sampling method, before and after training answered the psychological capital questionnaire (Luthans, Avolio, Avey, & Norman (2007).) and the the Job-Related Affective Well-Being Scale (Van Katwyk, Fox, Spector & Kelloway (2000). Teachers' psychological empowerment training package (Baum et al. (2018).) was performed in 10 sessions and 2 hours in each session, in a group method for the experimental group. For data analysis, simple mixed analysis of variance statistical method was used. Results: The results indicated that,in the short and long term teachers' psychological empowerment training package was effective in increasing psychological capital, positive dimension of job-related emotional well-being and in contrast was empirically effective in reducing negative teacher emotions, the negative aspect of job-related emotional well-being (p< 0/001). Conclusions: In summary, the results of the present study showed that the realization of teachers 'psychological empowerment concerns and the provision of essential prerequisites for professional development and growth in them is based on promoting teachers' psychological capital, strengthening coping resources and improving their mental resilience